'Working from Home' – Recent development trends in terraced housing design in a new suburban township in Malaysia. (2021) - Kholid, Mohd Fairus; Zaharin, Puteri Mayang Bahjah; Kasmuri, Kartini; Zahari, Muhammad Yasin Ramadhan
No abstract available